PERTANGGUNGJAWABAN PIDANA PELAKU PENISTAAN AGAMA MELALUI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Devit, Devit; Arman, Zuhdi (SCIENTIA JOURNAL, 2021)
ABSTRACT The case of blasphemy and blasphemy through social media is one of the negative impacts of technological development and globalization, as well as the negative manifestation of freedom and reform. The rise of blasphemy and blasphemy is coated with jokes that are widespread on social media such as instagram, facebook, and twitter. Many also use fake accounts to avoid being tracked. The desecration of religion is the trigger for the commission for the destruction of harmony and tranquility of both tribes, races, and religions themselves. In this law, blasphemy can be held accountable with the requirement to meet the elements contained in Article 28 paragraph (2) of Law No. 11 of 2008 on Information and Electronic Transactions that is anyone who issues a statement in the form of data or information that can burn anger and hatred against tribes, religions, races, intergroups (SARA). To overcome the act of blasphemy through the social media is not easy, but there are ways that can be applied in